Pitevní diagnóza Fabryho nemoci u heterozygotky, vedoucí k rozpoznání nediagnostikované manifestní nemoci v rodinĕ - Hůlková, H; Ledvinová, J; Poupĕtová, H; Bultas, J; Zeman, J; Elleder, M (Casopis lekaru ceskych, 1999)
The authors detected on necropsy in a 63-year-old woman with the clinical diagnosis of hypertension, atherosclerosis of the coronary and peripheral arteries, thromboembolism into the cerebral circulation and impaired cardiac conductivity lysosomal storage identified by histochemical and electronoptic analyses along with lipid chromatography as Fabry's disease. The stored lipids were neutral glycosphingolipids of the globo series globotriaosylceramide) and of the gala- series (galabiosylceramide) which accumulated as a result of deficient activity of the degrading enzyme alpha galactosidase A. Marked accumulation of these specific lipids was found in cardiomyocytes, in smooth muscles (of the media in arteries of the heart, kidneys, liver, spleen, lungs) in podocytes and mesangial cells of renal glomeruli, in epithelia of Henle's loop and in the distal tubules. In the vascular endothelium the storage was at the borderline of detectability. Accumulation did not lead to detectable organ disorders with the exception of the heart where it participated, no doubt, significantly in the cardiocyte hypertrophy. Examination of relatives revealed in the proband's son (age 41 years) a combination of renal, cardiac and skin changes typical for Fabry's disease which, however was not clinically diagnosed. The diagnosis was confirmed by proving of alpha-galactosidase A deficiency in the peripheral leucocytes and point mutation L293X in the VIth exon of the appropriate gene. In a granddaughter (age 15 years) biochemical and molecular genetic methods revealed the heterozygous state of Fabry's disease in preclinical stage.
Keywords: Fabry Disease; heterozygot; Male; Pedigree; rodokmen; Heterozygote; Adolescent; Fabryho nemoc; Adult; dospělí; mužské pohlaví; mladiství; pitva; lidé; ženské pohlaví; Humans; Female; lidé středního věku; Autopsy; Middle Aged